Pelatihan dan Pelayanan Perawatan Komplementer pada Kader Kesehatan Dan Ibu Dalam Meningkatkan Kesehatan Anak Balita Di Kecamatan Klungkung Kabupaten Klungkung - Nyoman Ribek; Putu Susy Natha Astini; Ida Erni Sipahutar (Jurnal Pengabmas Masyarakat Sehat, 2019)
The background of community service is in the form of training and complementary care services for health cadres and mothers who have children under five because complementary care is still not socialized to the community in terms of policies that have existed through government regulations since 2014. Complementary care is very effective to prevent and overcome child health problems toddlers such as  Upper respiratory tract infection are the main cause of death in children under five. Other health problems that can be prevented and treated include insomnia, difficulty eating, flatulence and a cold cough. If this problem concerns toddlers in a sustainable manner, it will interfere with Toddler's growth and development. To prevent and overcome these health problems, the empowerment of health cadres and mothers who have toddlers is very important, one of which is to provide training. The methods used in training are lectures, discussions and practices. By using a sample of 40 trained health cadres and 40 under-five mothers who received complementary care and counseling services. The results of the pre-test and post-test data were analyzed using paired-samples t test and the result was a significant increase in knowledge because the results obtained were significant values (p) = 0.001 (p 0.05).  It was concluded that the knowledge of complementary care for health cadres is very important because it can help socialize to mothers who have children under five, thus health problems such as runny stones, difficulty eating, insomnia, shortness of breath and flatulence can be prevented from appearing. It is recommended that health cadres can continuously guide mothers who have children under five at least once a month so that the number of health problems such as  Upper respiratory tract infectioncan be reducedKeywords : Training and service, Complementary care, Health cadre and  Mother has a toddler